Female's Preferred Birth Interval in Uganda: What Are The Associated Factors? - Douglas Candia; Edward Musoke; Christabellah Namugenyi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Preferred birth intervals of females can have potential effects on several maternal and neonatal health outcomes. Therefore, this study aims to ascertain factors associated with preferred birth intervals among females in Uganda. The data utilized were obtained from the 2016 Uganda Demographic and Health Survey. The Pearson chi-square test and logistic regression model were used to identify independent variables significantly associated with preferred birth intervals. The results showed that the majority of females or 77.1% preferred birth intervals of at least two years. The independent factors that significantly influenced their preferences included age group, region, education level, children ever born, contraceptive use and intention, marital status, as well as current employment status. Therefore, interventions aimed at educating females about birth intervals should be tailored to the specific regions, considering their education and level of exposure to contraceptives. This knowledge will enable females to understand the information provided, which is key to making healthy choices consistent with WHO recommendations.